(untitled) (Research, Society and Development, 2021)
The situational diagnosis is considered a potential tool for strengthening interprofessionality. Therefore, the objective of the present study was to describe its importance to strengthen interprofessionality among students in order to increase the interest of the Family Health Strategy in the theme in association with the claim for a humanized practice, as recommended by the guidelines of the Unified Health System. The instruments used in data collection were the Readiness for Interprofessional Learning Scale (RIPLS), a scale that assesses students’ adherence to interprofessionality and a complementary questionnaire on the socioeconomic and demographic situation, both applied between July and August of 2020 through the Google Forms platform with online signature of the consent form (number 3.623.996). The results of RIPLS were positive for interprofessionality in the three factors evaluated: teamwork and collaboration (factor 1), professional identity (factor 2) and patient-centered health care (factor 3). The factor 2 got the lowest score. It was concluded that situational diagnosis is a tool capable of strengthening interprofessionality by enabling students, teachers and health professionals to combine their experiences and knowledge to solve health problems arising from the community.